2015
DOI: 10.1016/j.nima.2014.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Calculations and measurements of the scintillator-to-water stopping power ratio of liquid scintillators for use in proton radiotherapy

Abstract: Liquid scintillators are a promising detector for high-resolution three-dimensional proton therapy dosimetry. Because the scintillator comprises both the active volume of the detector and the phantom material, an ideal scintillator will exhibit water equivalence in its radiological properties. One of the most fundamental of these is the scintillator’s stopping power. The objective of this study was to compare calculations and measurements of scintillator-to-water stopping power ratios to evaluate the suitabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…In addition, we measured and calculated the stopping power ratio, S , scin water to be 0.995 ± 0.001. This ratio matched that found in an independent study recently conducted by our group, within the respective standard deviations (Ingram et al 2015). It is worth mentioning that the original calculated S scin water differed by only 0.4%.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, we measured and calculated the stopping power ratio, S , scin water to be 0.995 ± 0.001. This ratio matched that found in an independent study recently conducted by our group, within the respective standard deviations (Ingram et al 2015). It is worth mentioning that the original calculated S scin water differed by only 0.4%.…”
Section: Discussionsupporting
confidence: 90%
“…This liquid scintillator, with a density of 0.963 g/cm 3 , serves as both a phantom and a detector medium (Ingram et al 2015). The peak emission wavelength of the scintillator is around 420 nm with a decay time of 1.4 ns and quantum yield of 0.83.…”
Section: Methodsmentioning
confidence: 99%
“…Early work with volumetric liquid scintillation detectors for 3D dosimetry showed that these detectors have several promising features (Beddar et al 2009). First, they are tissue- or water-equivalent, enabling dose detection with minimal field perturbation (Ingram et al 2015). Second, they have high spatial resolution (Archambault et al 2012).…”
Section: Introductionmentioning
confidence: 99%